Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/jjco/hyz146
|View full text |Cite
|
Sign up to set email alerts
|

Identification of serum microRNAs predicting the response of esophageal squamous-cell carcinoma to nivolumab

Abstract: Background Nivolumab, a programmed cell death protein 1 (PD-1) inhibitor, showed promising activity for the treatment of advanced esophageal squamous-cell carcinoma in a phase II study (ONO-4538-07; JapicCTI­No.142422). We explored serum microRNA (miRNA) candidate predictive markers of the response to nivolumab. Methods In the phase II study, 19 patients received nivolumab (3 mg/kg IV Q2W) at National Cancer Center Hospital. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…On other hand, down regulation of miR‐320b and miR‐375 was associated with delayed response for nivolumab treatment 143 . In similar line, high level of miR‐1233‐5p was associated with poor response of advanced esophageal squamous cell carcinoma for nivolumab 144 . Similarly overexpression of miR‐222 was correlated with lower therapeutic efficacy of ipilimumab (anti‐CTLA4) 145 in metastatic melanoma.…”
Section: Ncrna As Predictive Marker Of Therapy Outcomementioning
confidence: 87%
“…On other hand, down regulation of miR‐320b and miR‐375 was associated with delayed response for nivolumab treatment 143 . In similar line, high level of miR‐1233‐5p was associated with poor response of advanced esophageal squamous cell carcinoma for nivolumab 144 . Similarly overexpression of miR‐222 was correlated with lower therapeutic efficacy of ipilimumab (anti‐CTLA4) 145 in metastatic melanoma.…”
Section: Ncrna As Predictive Marker Of Therapy Outcomementioning
confidence: 87%
“…A phase 2 study that explored the efficacy of nivolumab, a PD-1 inhibitor, in esophageal squamous cell carcinoma revealed that serum miR-1233-5p levels (AUC = 0.895) before nivolumab treatment and miR-6885-5p, miR-4698, and miR-128-2-5p levels (AUC of 0.93, 0.97, and 0.93, respectively) after treatment initiation predicted response to ICI. 134 Though this was a small study, the evidence indicates the usability of ncRNAs for future prospective clinical trials. By investigating the differences of pretreatment circulating miRNAs between responders and non-responders in patients with NSCLC who received anti–PD-1 immunotherapy, Shukuya et al developed a response-predicting miRNA signature that consists of miR-199a-3p, miR-21-5p, and miR-28-5p.…”
Section: Non-coding Rnas As Biomarkers For Therapy Resistancementioning
confidence: 91%
“…Sudo and colleagues [97] propose a panel of six miRNA as a serologic test to diagnose ESCC at early stage: in their results, serologic levels of miR-8073, miR-3196 and miR-744-5p were higher, while serological levels of miR-6820-5p, miR-6794-5p and miR-6799-5p were lower in ESCC patients than in controls. Finally, levels of circulating miR-1233, miR-6885-5p, miR-4698 and miR-128-2-5p have predictive significance, being associated with response to nivolumab [98].…”
Section: Othersmentioning
confidence: 96%